FAMILY SYRPHIDAE - Montoya, Augusto L. (Zootaxa, 2016)
This paper is an updated Catalogue of Syrphidae from Colombia, including 337 species belonging to 3 subfamilies, 11 tribes, 57 genera and 16 subgenera. Each species is listed under its current accepted taxon, including the original reference, type locality, distribution by state/province in Colombia, in addition to a complete bibliographic reference. Species in the genera Calostigma, Claraplumula, Eristalinus, Fazia, Hermesomyia, Hybobathus, Mimocalla, Menidon, Monoceromyia, Orphnabaccha, Pelecinobaccha, Peradon, Rhinoprosopa, Sphiximorpha and Styxia are listed for the first time from Colombia. The advance in the knowledge of the Colombian Syrphidae is briefly discussed.